El carácter ambiguo del concepto de genocidio: Entre la Sociología y el Derecho. Un análisis a partir de la discusión alrededor del genocidio político - Benavides Vanegas, Farid Samir (2019)
In this paper, the author focuses on treatment that genocide receives from the field of sociology, then he checks the differences of sociological studies with legal regulation contained in Convention on the Prevention and Punishment of Genocide, specifically to groups that are subject to protection in legal definition of genocide.To achieve his purpose, the author develops how the process of production of the Convention was as well the criticism of legal definition of genocide in sociology. The author concludes sociological definitions have limitations, gives primacy to legal concept of genocide and affirms that social groups not protected by the Convention find protection by other rules of International Criminal Law.